Dual-wavelength fluorescence study of in vivo accumulation and formation of 5-ALA-induced porphyrins - V. E. Zavedeeva; K. T. Efendiev; D. M. Kustov; L. Yu. Loschenova; V. B. Loschenov (Biomedical Photonics)
This article discusses the processes of 5-aminolevulinic acid (5-ALA) metabolism, as well as the accumulation and photobleaching of protoporphyrin IX (PpIX) during photodynamic therapy (PDT) of benign skin tumors using the application method of introducing a 20% 5-ALA solution. The exposure time of the drug was 4 h. The study included two patients, one with dermatofibroma and one with congenital melanocytic nevus. Spectral fluorescence study was performed by fluorescence excitation using lasers at wavelengths of 405 and 632.8 nm. Fluorescence of normal and pathological tissues was recorded in the range of 350-800 nm at λexc =405 nm and in the range of 600-750 nm at λexc =632.8 nm. The dynamics of PpIX accumulation was studied. In the superficial tissue layers (at λexc =405 nm), the maximum accumulation of PpIX was recorded 3 h after the 5-ALA administration. In deeper tissue layers (at λexc =632.8 nm), the PpIX accumulation increased during 4 h of observation. After PDT with laser radiation with a wavelength of 635 nm, photobleaching of PpIX and the formation of its chlorin-type photoproducts with a fluorescence maximum in the range of 670–700 nm were observed. It was not possible to establish the presence of uroporphyrins I and III and/or coproporphyrin I, which could indicate a disturbance in the mitochondrial metabolism of necrotic cells. The obtained results expand the possibilities of spectral-fluorescent diagnostics and can contribute to increasing the effectiveness of 5-ALA-PDT of tumors.